The prognostic value of adipose tissue fatty acids for incident cardiovascular disease: results from 3944 subjects in the Scottish Heart Health Extended Cohort Study. - Woodward, M; Tunstall-Pedoe, H; Batty, G; Tavendale, R; Hu, F; Czernichow, S (2011)
AIMS: Dietary fats are routinely considered key determinants of cardiovascular risk, yet the scientific basis of this association has never been demonstrated using objective measures of fat intakes in a large prospective study in a general population. METHODS AND RESULTS: Adipose tissue was taken from 3944 participants, predominantly aged 40-59 years, in Scotland, 1984-87. Percentages of individual fatty acids were measured using gas chromatography. Over a median of 19.5 years, 870 incident cardiovascular disease (CVD) events occurred. Hazard ratios (HRs) were obtained from Cox models and the additional prognostic value, accounting for variables in the Framingham and ASSIGN CVD risk scores, were assessed using discrimination indices. Adjusting for age, sex, total and HDL-cholesterol, systolic blood pressure, smoking, hypertensive medication use, diabetes, socio-economic status and family history, the percentage of monounsaturated adipose tissue fatty acids had a positive log-linear relationship with incident CVD: the HR comparing risk between the fourth and first quartiles was 1.29 (95% confidence interval: 1.05, 1.59). n-3 polyunsaturated fat showed the reverse trend, the corresponding result being 0.77 (0.63, 0.94). These two composite variables improved the classification of incident CVD events by 1.0 and 6.4%, respectively, with only the latter being significant at the 5% level. CONCLUSIONS: A diet which is proportionately rich in polyunsaturated fat, as opposed to other fats, is expected to decrease the risk of CVD independently of the effects of common CVD risk factors, including social deprivation. Taking account of such diets improves the classification of future CVD events.